Economic and Cultural Values: Similarities and Differencies - Pruskus, Valdas (Problemos, 2004)
The article discusses peculiarities of economical and cultural values and specific features of their expression. With the help of a phenomenon of an art museum as an example of cultural and economical values the author tries to define the main peculiarities of the above mentioned values. The author maintains that economic values have objectives, distinctly definable according to the agreed standards. These objectives are directed to gain the profit, which exists in reality and is acknowledged by everyone, so that there is no doubt concerning its quality, properties and value. Meanwhile cultural value is not defined in the same way according to the accepted and arranged standards; it is not related to the gain of material profit and is not understood by everyone in the same way, and a lot of arguments take place concerning its quality and value. These differences partly influence distinct attitudes of individuals towards its value. In spite of this, there is no doubt concerning the importance of cultural values for the spiritual and social progress of both an individual and society. Furthermore, cultural values form the “culture capital” itself, without which it is difficult to imagine even creation and increase of economical capital of society.
Keywords: economical and cultural values; theory of social value; cultural product; economical assessment of cultural value; consumer of cultural values